Spotting dan Amenorea pada Akseptor KB Suntik 3 Bulan: Spotting and Amenorrhea in Acceptors of 3 Monthly Injectable Birth Control - Ana Riandari; Cahyaningrum; Masruroh (Journal of Holistics and Health Sciences, 2024)
Injectable contraception is the contraception most frequently used by family planning acceptors. Injectable birth control contraception, especially the 3 month injection contraceptive, has side effects, including spotting and amenorrhea. Based on the results of a preliminary survey conducted at TPMB Ari Budiyanti Ciberem, Banyumas. The majority use 3-month injectable contraceptives. Based on the results of initial interviews with 5 acceptors of 3-month injections at TPMB Ari Budiyanti, 4 acceptors said they had used 3-month injection contraception for more than 1 year and had not experienced menstruation. But there is 1 The acceptor said that in the first month of use the acceptor experienced menstrual disorders in the form of spotting bleeding, then in the following month he did not experience menstruation. The aim of the research was to find out the description of menstrual disorders in 3-month injection contraceptive acceptors at PMB Ari Budiyanti Ciberem Banyumas. Quantitative descriptive research design. The population in this study were mothers who were acceptors of 3-month contraceptive injections at PMB Ari Budiyanti, totaling 206 acceptors. The sampling technique uses purposive sampling technique so that the number of samples is 198 acceptors at PMB Ari Budiyanti. The research instrument uses a master table. Data analysis uses univarate analysis in the form of frequency distribution. The research results showed that the majority of 3-month injectable contraceptive users experienced the side effect of amenorrhea as many as 169 respondents (85.4%) and experienced the side effect of spotting as many as 29 respondents (14.6%). From this research, the majority of respondents experienced amenorrhea, 169 respondents (85.4%) and 29 respondents experienced spotting (14.6%). Suggestions for health workers are to add to and develop existing knowledge, especially regarding the characteristics of 3-month contraceptive injection acceptors with spotting and amenorrhea.   ABSTRAK Kontrasepsi Suntik merupakan kontrasepsi yang paling sering digunakan oleh Akseptor KB. Kontrasepsi KB suntik khusunya KB Suntik 3 Bulan memiliki efek sampingantara lain  spotting dan Amenorea.  Berdasarkan hasil survei pendahuluan yang dilakukan di TPMB Ari Budiyanti Ciberem, Banyumas,  Berdasarkan hasil wawancara awal dengan 5 akseptor suntik 3 bulan di TPMB Ari Budiyanti, 4 akseptor mengatakan lebih dari 1 tahun menggunakan kontrasepsi suntik 3 bulan dan tidak mengalami menstruasi. Tetapi ada 1 akseptor mengatakan pada penggunaan bulan pertama akseptor mengalami gangguan menstruasi berupa perdarahan bercak, kemudian pada bulan berikutnya tidak mengalami menstruasi.tujuan penelitian adalah  Untuk mengetahui gambaran gangguan menstruasi pada akseptor KB suntik 3 bulan di PMB Ari Budiyanti Ciberem Banyumas. Desain penelitian deskriptif kuantitatif. Populasi dalam penelitian ini adalah ibu yang menjadi akseptor KB suntik 3 bulan di PMB Ari Budiyanti yang berjumlah 206 Akseptor. Teknik sampling menggunakan Teknik purposive sampling sehingga jumlah sampel adalah 198 Akseptor di PMB Ari Budiyanti. Instrumen penelitian menggunakan master table. Analisa data menggunakan Analisa univarat dalam bentuk distribusi frekuensi. Hasil penelitian menunjukan bahwa Sebagian besar pengguna KB suntik 3 bulan mengalami efek samping amenorea sebanyak 169 respoden (85,4%) dan mengalami efek samping spotting sebanyak 29 responden (14,6%). dari penelitian ini adalah sebagian besar responden mengalami amenorea sebanyak 169 responden (85,4%) dan yang mengalami spotting sebanyak 29 responden (14,6%). Saran untuk tenaga kesehatan yaitu dapat menambah dan mengembangkan ilmu yang sudah ada terutama mengenai karakteristik akseptor KB suntik 3 bulan dengan Spotting dan Amenorea.